High-Current-Density field emission from self-heating printed carbon nanotubes. Issue 4 (2nd April 2016) - Wang, Qilong; Yu, Cairu; Di, Yusong; Zhu, Zhuoya; Zhang, Xiaobing; Li, Chen; Lei, Wei
ABSTRACT: High-current-density field emitters are considered as the potential and necessary components for compact high definition x-ray sources and high-power cold cathode microwave amplifiers. In this report, high-current-density field emission from self-heating printed carbon nanotubes is introduced. Large emission current causes large heat that increases the temperature of the emitters. The temperature is estimated to be more than ~1600 K. Localized surface field and high temperature both drive more electrons escaping from the emitters, and the maximum current density is larger than ~2.7 A/cm 2 that will satisfy the need of most vacuum electron devices including x-ray sources and microwave electron devices.